Maximization of monomeric C5 sugars from wheat bran by using mesoporous ordered silica catalysts. (August 2017) - Sánchez-Bastardo, Nuria; Alonso, Esther
Graphical abstract: Highlights: RuCl3 /Al-MCM-48 is an active catalyst for arabinoxylan hydrolysis. RuCl3 /Al-MCM-48 accelerates conversion of arabinoxylans into arabinose and xylose. RuCl3 /Al-MCM-48 catalysts inhibit further dehydration into furfural. Significant reduction in hydrolysis time from several hours to 15 min is achieved. A two-step process using RuCl3 /Al-MCM-48 maximizes C5 sugars from wheat bran. Abstract: The hydrolysis process of a real fraction of arabinoxylans derived from wheat bran was studied. The influence of catalyst type and loading, reaction time and different metal cations were discussed in terms of the hydrolysis yield of arabinose and xylose oligomers as well as the formation of furfural as degradation product. A high yield of arabinoxylans into the corresponding monomeric sugars (96 and 94% from arabino- and xylo-oligosaccharides, respectively) was obtained at relatively high temperatures (180 °C) and short reaction times (15 min) with a catalyst loading of 4.8 g of RuCl3 /Al-MCM-48 per g of initial carbon in hemicelluloses.